2018
DOI: 10.1002/tea.21506
|View full text |Cite
|
Sign up to set email alerts
|

Implicit STEM ability beliefs predict secondary school students' STEM self‐efficacy beliefs and their intention to opt for a STEM field career

Abstract: Despite the widely accepted view that low self-efficacy beliefs negatively influence students' intention to opt for a STEM field oriented study or career path, it remains unclear how to effectively stimulate these beliefs in students who do seem to have the ability and motivation to opt for a STEM career. A suggestion from previous literature is that students' implicit beliefs about the malleability of their learning ability can have a major impact on their self-efficacy beliefs, and, importantly, that these i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 57 publications
0
39
0
Order By: Relevance
“…Previous findings (Jansen, Scherer, & Schroeders, 2015) based on PISA 2006 data also support the positive association between science self‐efficacy and inquiry‐based learning opportunities. Given the important role of students' academic self‐efficacy in predicting academic achievement and even future involvement and occupation interests recognized in numerous studies (Britner & Pajares, 2006; Jansen et al, 2015; van Aalderen‐Smeets, van der Molen, & Xenidou‐Dervou, 2018), the use of inquiry‐based instructional practices in science classrooms is encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings (Jansen, Scherer, & Schroeders, 2015) based on PISA 2006 data also support the positive association between science self‐efficacy and inquiry‐based learning opportunities. Given the important role of students' academic self‐efficacy in predicting academic achievement and even future involvement and occupation interests recognized in numerous studies (Britner & Pajares, 2006; Jansen et al, 2015; van Aalderen‐Smeets, van der Molen, & Xenidou‐Dervou, 2018), the use of inquiry‐based instructional practices in science classrooms is encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…However, fewer studies tested the relationships among self-efficacy, outcome expectations, and career interest from an integrated STEM perspective (Nugent et al, 2015;van Aalderen-Smeets et al, 2018). Nugent et al (2015) found that in a crosssectional study that 10-to 14-year-old students' STEM interest predicted their STEM self-efficacy and outcome expectations.…”
Section: Self-efficacy Outcome Expectations and Stem Career Interestmentioning
confidence: 99%
“…Improving students' science knowledge and skills is therefore considered essential for the future research and innovation that underpins a society's competitiveness (Australian Academy of Science, ). Thus, targeting improvement in students' science outcomes has become a focal point of much research and policy (Van Aalderen‐Smeets, Walma van der Molen, & Xenidou‐Dervou, ; Watt et al, ). At the same time, however, declines in students' valuing of science and science achievement are evident in Australia (the site of the present study) and many other western countries (OECD, , ).…”
Section: Introductionmentioning
confidence: 99%